Digital interactive English teaching materials for Islamic senior high school students in Indonesia - Anggaira, Aria Septi; Madkur, Ahmad; Sari, Yeasy Agustina; Aryanti, Nurul; Syukron, Buyung (Edelweiss Applied Science and Technology, 2024)
This research aimed to develop interactive English teaching materials based on digital literacy for millennial Muslim learners. The study employed the Research and Development (R&D) approach, utilizing the Four-D (4D) model consisting of four stages: define, design, develop, and disseminate. The research involved 10 students and 1 English teacher as test users, along with experts in content/material and instructional media. Data were collected quantitatively through a product validation questionnaire. The outcome of the research is an interactive teaching e-book on digital literacy, validated by experts and tested with a small user group. Expert validators gave an average score of 4.8, while user testing yielded an average score of 4.4. This study concludes that the interactive English teaching materials, focusing on digital literacy for millennial Muslim learners, are suitable and valid for use in English language learning at the tenth-grade level in Indonesian Islamic high schools.